Peningkatan Hasil Belajar Ilmu Pengetahuan Alam Media Word Wall - Widya Novita Sari; Fatkhurrohman; Ali Mu'tafi (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
Low student achievement in science subjects is often caused by the use of unengaging and non-interactive learning media. This study aims to examine the effectiveness of using Wordwall media to improve science learning outcomes among fourth-grade students. Wordwall, a game-based interactive platform, was selected as it offers a fun and dynamic approach that is expected to enhance students’ motivation and understanding of the material. This research employed a quantitative approach with a quasi-experimental design, involving two groups: an experimental class using Wordwall media and a control class using conventional methods. Data were collected through pretests and posttests, observations, interviews, and documentation. The study involved two classes, Grade IV A and IV B, with 15 students in each class. The data were analyzed using descriptive and inferential statistics, including a t-test. The findings indicate that the use of Wordwall media significantly improved students’ science learning outcomes. This is evidenced by the t-test results showing that the t-value exceeded the critical value at both the 5% significance level (3.1441 > 2.1447) and the 1% level (3.1441 > 2.976). Therefore, it can be concluded that Wordwall media is effective in enhancing science learning outcomes for fourth-grade students at SD Takhassus Al-Qur'an Kalibeber.